Metaconcrete: designed aggregates to enhance dynamic performance - Mitchell, Stephanie J.; Pandolfi, Anna; Ortiz, Michael (Journal of the mechanics and physics of solids, 2014)
We propose a new type of concrete for the attenuation of elastic waves induced by dynamic excitation. In this metamaterial, which we call metaconcrete, the stone, sand, and gravel aggregates of standard concrete are replaced with spherical inclusions consisting of a heavy metal core coated with a soft outer layer. These engineered aggregates can be tuned so that particular frequencies of a propagating blast wave will activate resonant oscillations of the heavy mass within the inclusions. The resonant behavior causes the system to exhibit negative effective mass, and this interaction between the wave motion and the resonant aggregates results in the attenuation of the applied dynamic loading. We introduce the concept of negative mass by deriving the effective momentum mass for the system and we define the geometrical and material parameters for the design of resonant aggregates. We develop finite element models for the analysis of metaconcrete behavior, defining a section of slab containing a periodic arrangement of inclusions. By computing the energy histories for the system when subject to a blast load, we show that there is a transfer of energy between the inclusions and the surrounding mortar. The inclusions are able to absorb a significant portion of the applied energy, resulting in a reduction in the amount of stress carried by the mortar phase and greatly improving the ability of the material to resist damage under explosive dynamic loading.